TriTECM: A tetrafunctional T-cell engaging antibody with built-in risk mitigation of cytokine release syndrome - Carrara, Stefania C.; Harwardt, Julia; Grzeschik, Julius; Hock, Björn; Kolmar, Harald (Frontiers in Immunology, 2022)
Harnessing the innate power of T cells for therapeutic benefit has seen many shortcomings due to cytotoxicity in the past, but still remains a very attractive mechanism of action for immune-modulating biotherapeutics. With the intent of expanding the therapeutic window for T-cell targeting biotherapeutics, we present an attenuated trispecific T-cell engager (TCE) combined with an anti- interleukin 6 receptor (IL-6R) binding moiety in order to modulate cytokine activity (TriTECM). Overshooting cytokine release, culminating in cytokine release syndrome (CRS), is one of the severest adverse effects observed with T-cell immunotherapies, where the IL-6/IL-6R axis is known to play a pivotal role. By targeting two tumour-associated antigens, epidermal growth factor receptor (EGFR) and programmed death ligand 1 (PD-L1), simultaneously with a bispecific two-in-one antibody, high tumour selectivity together with checkpoint inhibition was achieved. We generated tetrafunctional molecules that contained additional CD3- and IL-6R-binding modules. Ligand competition for both PD-L1 and IL-6R as well as inhibition of both EGF- and IL-6-mediated signalling pathways was observed. Furthermore, TriTECM molecules were able to activate T cells and trigger T-cell-mediated cytotoxicity through CD3-binding in an attenuated fashion. A decrease in pro-inflammatory cytokine interferon γ (IFNγ) after T-cell activation was observed for the TriTECM molecules compared to their respective controls lacking IL-6R binding, hinting at a successful attenuation and potential modulation via IL-6R. As IL-6 is a key player in cytokine release syndrome as well as being implicated in enhancing tumour progression, such molecule designs could reduce side effects and cytotoxicity observed with previous TCEs and widen their therapeutic windows.